Assessment of Food Security Status of Goat Farmers In Lagos State, Nigeria - Akintobi, O.S.; Achu, B.C. (Department of Agronomy and Horticulture, IPB University, 2021)
The goat value chain plays a pivotal role in income and employment generation, livelihood enhancement; food and nutrition security among the poor, marginalized and disadvantaged groups and they are reared to supplement income and as a means of reducing food insecurity. The objective of this study is to assess the food security status of urban goat farmers in some local government areas of Lagos state, Nigeria. The use of qualitative method of data collection in the form of structured questionnaires were executed during the course of this study on a sample size of 80 goat farmers. Furthermore, during the course of the study, the specific objectives were analyzed using descriptive statistics as well as USDA food security code module. Using the Pearson’s rank correlation and binary logistic regression, the hypotheses were accurately tested to achieve results. From the result acquired, it was determined that men dominated women in the goat farming sector as well as revealing that the average age of respondents were 42.4 years. Furthermore, the results revealed that, about 65.4% of the respondents made an annual income ranging from 100,000-300,000 Naira and have been residents of the sample location for about 10-15 years. Another observation made from the results obtained during the course of this study showed that majority of the respondents practiced semi intensive system of management. This involves them using family labor (55.6%), having an average of 18.8 goats, as well as revealing sales as their main purpose of farming. More revelations from the result showed that, majority of the respondents were food insecure without hunger. Showing the major reasons for food insecurity to be insufficient finance, high cost of food and poor storage and processing. It was recommended that farmers be encouraged to belong to organizations such as cooperatives to solve problems in management and also for easy access or contact by government and extension agents.